ANTIBAKTERI SENYAWA FENOLIK DARI ALANG -ALANG (IMPERATA CYLINDRICA) - Sinurat, Jhon Patar; Wulandari, Suci; Berutu, Rinaldo (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Phytochemical screening test proved that the extract of Reeds (Imperata cylindrica) contained phenolic compounds tested using 5% FeCl3 reagent. Antibacterial test using agar diffusion method against Reeds extract in DMSO solvent. The phenolic compounds obtained from the saputangan leaves Reeds extract were 36.96 grams after undergoing maceration. Reeds extract of phenolic compounds with concentrations (200; 100; 50 and 25 ppm) had strength antibacterial where the average inhibition zone of Staphylococcus aureus bacteria was 10.0 mm and the average inhibition zone was at Escherichia coli bacteria measuring 10.3 mm.